2020 IEEE International Conference on Robotics and Automation (ICRA) 2020
DOI: 10.1109/icra40945.2020.9197457
|View full text |Cite
|
Sign up to set email alerts
|

Designing Ferromagnetic Soft Robots (FerroSoRo) with Level-Set-Based Multiphysics Topology Optimization

Abstract: Soft active materials can generate flexible locomotion and change configurations through large deformations when subjected to an external environmental stimulus. They can be engineered to design 'soft machines' such as soft robots, compliant actuators, flexible electronics, or bionic medical devices. By embedding ferromagnetic particles into soft elastomer matrix, the ferromagnetic soft matter can generate flexible movement and shift morphology in response to the external magnetic field. By taking advantage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Soft magnetic skin is a composite material composed of small magnetic particles embedded in a soft polymer matrix. [53][54][55][56] The magnetic skin is on the skin beside the ramus, which is the junction of the mandible and sternocleidomastoid muscle. When a subject (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Soft magnetic skin is a composite material composed of small magnetic particles embedded in a soft polymer matrix. [53][54][55][56] The magnetic skin is on the skin beside the ramus, which is the junction of the mandible and sternocleidomastoid muscle. When a subject (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Through rigorous analysis and experimental validation, the authors showed that the proposed framework showcases its effectiveness in realizing topologically optimized designs. The authors previously implemented topology optimization using a traditional level set and reconciled level set method for ferromagnetic soft robots [329,330].…”
Section: Topology Optimizationmentioning
confidence: 99%
“…In addition to high conductivity, stretchability, and transmittance, the conformable contact between the electrode and the free-form human skin surface [55,56] is also essential in electrode development. The conformable contact can help achieve low electrode-skin impedance and acquire high-fidelity EMG signals [50,57] during dynamic and subtle lip movements.…”
Section: Design Fabrication and Characterization Of Emg Sensing Elect...mentioning
confidence: 99%